PELATIHAN MANAJEMEN KEUANGAN SEDERHANA BAGI KARYAWAN CV AJIB BIO SYIFA - Octa Nilam Lukkita Aga (Institut Bisnis Muhammadiyah Bekasi, 2022)
The purpose of this PKM or Community Service program is to provide knowledge and skills regarding financial management to employees of PT. Ajib Bio Syifa. The specific target is to provide knowledge and skills in business development through guidance and training in improving or improving financial management. The prospects for business development are reviewed based on financial analysis. PKM program activity plan is to conduct socialization to PT. Ajib Bio Syifa, prepares training facilities that can support the success of PKM, provides guidance to management actors in preparing financial reports, conducts training in order to improve skills and knowledge, either through workshops or other activities, and monitors and evaluates activities to support success and business continuity.